Does Distance Matter? An Investigation of Partners Who Audit Distant Clients and the Effects on Audit Quality† - Francis, Jere R.; Golshan, Nargess; Hallman, Nicholas J. (Contemporary Accounting Research, 2022)
ABSTRACT We examine how audit partners' geographic proximity to clients affects audit quality. We use hand‐collected data to show that approximately half of audit partners are assigned to clients headquartered more than 100 km away from the partners' home locations. Few of these partners relocate after receiving their assignments and, as a result, more than one‐third of clients are audited by partners who must commute long distances to visit the client in person. We explore this phenomenon by first modeling how distance affects partner‐client matching. We find that partners' geographic proximity to a prospective client is an important matching criterion, but also that trade‐offs are made when other partner characteristics such as industry specialization are more likely to be important. Next, consistent with our prediction, we show that audit quality is lower when partners reside farther from their clients. We corroborate our primary findings by showing that the association between partner distance and audit quality is mitigated when partners have access to direct flights to their clients' headquarters and when clients are geographically dispersed. Our paper should be informative for regulators, practicing auditors, and academics interested in how partner‐client matching affects audit outcomes.